The Impact of Financial Profitability Ratio to the Stock Returns of Telecommunication Company during the COVID-19 Pandemic in Indonesia - Adelia Putri Pratiwi; Ana Noveria (ARKA INSTITUTE, 2023)
COVID-19 has become a major pandemic striking the world with shocking effects. These strikes resulted in deaths of a lot of people across the globe and also forced people to adopt a new way of life. Not only lifestyle, this pandemic is also affecting all sectors of people’s lives, especially in economic and business sectors. This study focuses on the impact of the COVID-19 pandemic on firms financial performance and stock price in the telecommunication sector in Indonesia. In this case, it focuses on the profitability ratio. The independent variables include on this study are ROA, ROE, ROCE, ROIC, NPM, OPM, and GPM while the stock return becomes the dependent variables. The data is processed towards panel data regression and divided the timeline into 3 periods, pre-pandemic periods (2017-2019) and post-pandemic periods (2020-2022) and overall periods (2017-2022). This study found that in overall period model, pre-pandemic, and post pandemic model, none of the dependent variables significantly affect stock returns partially. Simultaneously, the profitability financial ratios also do not affect stock return significantly.